Disseminated Malaria- Case Report (Indian Internet Journal of Forensic Medicine and Toxicology, 2009)
Malaria is an endemic disease in the costal belt of Karnataka. Sudden death due to malaria is rare, but reported. Here we present a case of sudden death in a 50 year old male who was found dead in a room. Crime scene investigation, autopsy report, histopathological examination and chemical analysis confirmed the cause of death as disseminated malaria.
Keywords: Malaria; Disseminated malaria; Sudden death; Coastal